What We Write about When We Write About AAC: The Past 30 Years of Research and Future Directions. (2nd October 2015) - McNaughton, David; Light, Janice
ABSTRACT: For the past 30 years, the Augmentative and Alternative Communication (AAC) journal has both documented and instigated change in the field of AAC. We reviewed the papers published in the AAC journal from1985–2014 in order to identify trends in research and publication activities. Intervention research made up the largest proportion of the four types of research (i.e., intervention, descriptive, experimental, and instrument and measurement development) reported in the journal. Intervention research has most commonly focused on the individual with complex communication needs, and most frequently on younger individuals (aged 17 and younger) with developmental disabilities. While much has been learned in the past 30 years, there continues to be a need for high quality research in a large number of areas. There is a special need for reports of interventions with older individuals with complex communication needs as a result of acquired disabilities, and for information on effective interventions for the communication partners of persons with complex communication needs.